174k views
3 votes
Rearrange the equation so x is the independent variable. y+6=5(x-4)

User EMi
by
5.3k points

2 Answers

4 votes

Answer:

y = 5x - 26

Explanation:

Since x is the independent variable, you have to solve for y.

y + 6 = 5(x-4)

Now distribute:

y + 6 = 5x - 20

subtract the 6 from both sides

y + 6 - 6 = 5x - 20 - 6

y = 5x - 26

User Jonauz
by
5.0k points
5 votes

Answer:

x = (y + 26)/5

Explanation:

Order of Operations: BPEMDAS

Step 1: Write out equation

y + 6 = 5(x - 4)

Step 2: Distribute

y + 6 = 5x - 20

Step 3: Isolate x

y + 26 = 5x

Step 4: Isolate variable x

(y + 26)/5 = x

Step 5: Rewrite

x = (y + 26)/5

User Faysal
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.